CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

The inverse of the statement $$(p \wedge \sim q)  \rightarrow r$$ is


A
(pq)r
loader
B
(pq)r
loader
C
(pq)r
loader
D
None of these.
loader

Solution

The correct option is D $$(\sim p \vee q) \rightarrow \sim r$$
The inverse of the statement $$(p \wedge \sim q)  \rightarrow r$$ is,
$$\equiv \sim (p \wedge \sim q)  \rightarrow \sim r \equiv (\sim p \vee \sim (\sim q)) \to \sim r$$
$$\equiv (\sim p \vee q) \to \sim r$$

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
People also searched for
View More



footer-image